Optical laminate and organic el display device comprising same

通过在光学层叠体的圆偏振板上层叠第3保护膜并控制保护膜的尺寸变形率,解决了光学层叠体在恒温恒湿环境下产生正卷曲的问题,实现了抑制气泡混入和提高图像显示 Quality effect.

CN119439343APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410989948.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-07-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing optical laminate is prone to curling in a constant temperature and humidity environment, resulting in tiny bubbles generated at the end of the optical laminate when it is bonded to the display element, affecting the image display quality.

Method used

By stacking the third protective film on the first polarizer protective film side of the circular polarization plate, the size deformation rate of the first, second and third protective films is controlled, and a specific relationship is satisfied to suppress the occurrence of positive curl.

Benefits of technology

It effectively suppresses the curling of the optical laminated body during time, prevents the inclusion of tiny bubbles when bonding to the display element, and improves the quality and stability of image display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119439343A_ABST
    Figure CN119439343A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: an optical laminate which is capable of suppressing the occurrence of positive curl over time and suppressing the mixing of microbubbles at the end of the optical laminate when bonded to a display element; and an organic EL display device which includes the optical laminate. The optical laminate has a first polarizer protective film, a first adhesive layer, a polyvinyl alcohol-based polarizing film, a second adhesive layer, and a second polarizer protective film adjacent to each other in this order. A third protective film is laminated on the first polarizer protective film side of the circular polarizing plate comprising a first adhesive layer and a phase difference film formed of a polymer of a polymerizable liquid crystal compound through a second adhesive layer, and the thickness of the phase difference film is 0.5-10 [mu] m. The dimensional deformation rate (H1) of the first polarizer protective film, the dimensional deformation rate (H2) of the second polarizer protective film, and the dimensional deformation rate (H3) of the third polarizer protective film after 48 hours in an environment with a temperature of 40 DEG C and a relative humidity of 60% satisfy formula (1) and formula (2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and a display device including the optical layered body. Background Art

[0002] A circular polarizing plate is an optical component formed by laminating a polarizing plate and a phase difference plate, and is used, for example, in an image display device such as an organic EL image display device, to cut off reflected light from an electrode constituting the device to improve observability. In the past, a circular polarizing plate formed by laminating a phase difference plate via an adhesive layer on a polarizing plate having a polarizer protective film laminated on both sides of the polarizer was widely used, and an optical laminate having an adhesive layer provided on the phase difference plate side in order to laminate such a circular polarizing plate on a display element is known (e.g., Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-96970 Summary of the invention

[0006] Problems to be solved by the invention

[0007] As a polarizer protective film disposed on both sides of the polarizer, from the perspective of the desired function, handling, etc., sometimes the constituent materials and thicknesses of polarizer protective films are used in combination. In an optical laminate having different polarizer protective films laminated on both sides of such a polarizer, even in an environment such as a clean room environment where a relatively constant temperature and humidity is maintained, sometimes a large amount of so-called positive curling is produced in which the phase difference plate side becomes convex and warped over time. In an optical laminate having such positive curling, it is easy to draw in air when attached to a display element and produce tiny bubbles at the end of the laminate, which sometimes leads to poor display in an image display device.

[0008] An object of the present invention is to provide an optical layered body which can suppress the occurrence of positive curl over time and suppress the incorporation of fine bubbles into the edge of the optical layered body when bonded to a display element.

[0009] Means for solving problems

[0010] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention. That is, the present invention includes the following aspects.

[0011] [1] An optical laminate, comprising a circularly polarizing plate having a first polarizer protective film, a first adhesive layer, a polyvinyl alcohol-based polarizing film, a second adhesive layer, a second polarizer protective film, a first tackiness adhesive layer, and a retardation film formed of a polymer of a polymerizable liquid crystal compound adjacent to each other in this order, wherein a third protective film is laminated on the first polarizer protective film side via a second tackiness adhesive layer,

[0012] The thickness of the retardation film is 0.5 to 10 μm.

[0013] The dimensional deformation rate (H1) of the first polarizer protective film, the dimensional deformation rate (H2) of the second polarizer protective film, and the dimensional deformation rate (H3) of the third polarizer protective film after 48 hours under an environment of a temperature of 40° C. and a relative humidity of 60% satisfy the following equations (1) and (2):

[0014] -0.300≤H1-H2≤-0.001 (1)

[0015] -0.040≤(H3+H1)-H2≤0.100 (2).

[0016] [2] The optical laminate according to [1], wherein the thickness (T2) of the second polarizer protective film and the thickness (T3) of the third protective film satisfy the following formula (3):

[0017] 45≤(T3 / T2) ×100≤350 (3).

[0018] [3] The optical layered body according to [1] or [2] above, wherein the thickness of the third protective film is 10 to 100 μm.

[0019] [4] The optical layered body according to any one of [1] to [3], further comprising a cured resin layer on the side of the third protective film opposite to the circularly polarizing plate side.

[0020] [5] The optical layered body according to any one of [1] to [4] above, wherein the third protective film is a triacetylcellulose film or a polymethyl methacrylate polymer film.

[0021] [6] The optical layered body according to any one of [1] to [5], wherein a peeling force when the third protective film is peeled off from the optical layered body is 1 N / 25 mm or more.

[0022] [7] An organic EL display device comprising the optical layered body described in [1] above.

[0023] Effects of the Invention

[0024] According to the present invention, it is possible to provide an optical layered body which can suppress the occurrence of positive curl over time and suppress the mixing of fine bubbles at the edge of the optical layered body when bonded to a display element. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic cross-sectional view showing an example of the layer structure of the optical layered body of the present invention. DETAILED DESCRIPTION

[0026] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope that does not impair the gist of the present invention.

[0027] <Optical laminate>

[0028] like Figure 1 As shown, the optical laminate 13 of the present invention includes a circular polarizing plate 12, and the circular polarizing plate 12 is formed by stacking the first adhesive layer 6 and the phase difference film 7 formed by the polymer of the polymerizable liquid crystal compound on the polarizing plate 11 including the first polarizer protective film 1, the first adhesive layer 2, the polyvinyl alcohol polarizing film 3, the second adhesive layer 4, and the second polarizer protective film 5. In addition, the third protective film 9 is provided on the side of the first polarizer protective film 1 of the circular polarizing plate 12 via the second adhesive layer 8. The second adhesive layer and the third protective film are usually located in adjacent positions. In order to protect the polyvinyl alcohol polarizing film (hereinafter, also referred to as "polarizing film"), the optical laminate of the present invention is provided with a third protective film in addition to the first polarizer protective film and the second polarizer protective film provided on both sides of the polarizing film. By controlling the dimensional deformation rate of these three protective films, the occurrence of warping of the optical laminate over time can be suppressed. When the optical laminate of the present invention is assembled into an image display device, etc., the third protective film 9 is usually not peeled off from the optical laminate 13, but is assembled into the image display device, etc. as a component of the optical laminate 13. For example, a front panel, etc. can be laminated on the surface of the third protective film on the opposite side of the first adhesive layer via a bonding adhesive layer.

[0029] The optical laminate of the present invention may include other layers for constituting the optical laminate, except for the first polarizer protective film (hereinafter, also referred to as "the first protective film"), the first adhesive layer, the polarizing film, the second adhesive layer, the second polarizer protective film (hereinafter, also referred to as "the second protective film"), the first adhesive layer, the phase difference film formed by the polymer of the polymerizable liquid crystal compound (hereinafter, also referred to as "phase difference film"), the second adhesive layer and the third protective film, as long as the effect of the present invention is not affected. Other layers are, for example, layers that can be stacked on the outside of the third protective film (the side opposite to the second adhesive layer) and / or the outside of the phase difference film (the side opposite to the first adhesive layer), for example, a cured resin layer (hard coating layer, etc.) for protecting the polarizing film, the optical laminate, an optical compensation layer, the second phase difference layer, another (adhesive) adhesive layer other than the above-mentioned first (adhesive) adhesive layer and the second (adhesive) adhesive layer, a substrate layer, etc.

[0030] In the present invention, when the dimensional deformation rate of the first protective film after 48 hours in an environment of a temperature of 40° C. and a relative humidity of 60% is defined as H1 and the dimensional deformation rate of the second protective film is defined as H2, H1 and H2 satisfy the following formula (1):

[0031] -0.300≤H1-H2≤-0.001 (1).

[0032] When the dimensional change rate H1 of the first protective film and the dimensional change rate H2 of the second protective film satisfy the above formula (1), there is a slight difference between the dimensional change rate of the first protective film and the dimensional change rate of the second protective film. If there is such a difference in the dimensional change rate of the two protective films located on both sides of the polarizing film via the adhesive layer, it is easy to produce warping (positive curl) that makes the second protective film side convex. Such warping often occurs over time, and sometimes it occurs even in a relatively constant temperature and humidity environment such as a clean room. For example, if warping occurs during storage, air may be drawn in when it is assembled into an image display device and bonded to a display element, etc., causing poor display in the image display device.

[0033] Generally, the smaller the value of H1-H2 in the range of formula (1), the greater the difference in the dimensional change rate between the first protective film and the second protective film. Therefore, it is believed that the closer the value of H1-H2 is to -0.300, the easier it is to produce positive curl over time. In the present invention, as described later, by providing a third protective film that meets specific conditions on such a polarizing plate that easily produces positive curl over time, the effect of suppressing the occurrence of the above-mentioned positive curl is excellent. In the present invention, the value of H1-H2 can be, for example, greater than -0.300 and less than -0.005, or greater than -0.300 and less than -0.01. In the case of including such a polarizing plate, the effect of the present invention can be more significantly manifested.

[0034] In the present invention, when the dimensional deformation rate of the third protective film after 48 hours in an environment of a temperature of 40° C. and a relative humidity of 60% is defined as H3, H1, H2, and H3 satisfy the following formula (2):

[0035] -0.040≤ (H3+H1)-H2≤0.100 (2).

[0036] As described above, the polarizing plate satisfying formula (1) is prone to positive curling over time due to the difference in the dimensional change rate of the two protective films located on both sides of the polarizing film. Formula (2) means that the total dimensional change rate (H3+H1) of the two protective films (the first protective film and the third protective film) stacked on one side of the polarizer becomes equal to the dimensional change rate (H2) of the second protective film stacked on the other side of the polarizer. The optical laminate of the present invention is constructed in a manner that the dimensional change rate of each protective film located on both sides of the polarizer satisfies the above relationship, and has a high inhibitory effect on the generation of the above-mentioned positive curling over time.

[0037] If the sum of the dimensional change rates of the first protective film and the third protective film is equal to the dimensional change rate of the second protective film, the generation of positive curling over time can be effectively suppressed. Thus, even after long-term storage for example for more than 6 months, the incorporation of microbubbles at the end of the optical laminate when the display element is bonded can be suppressed. The value of (H3+H1)-H2 is preferably above -0.030 and below 0.080, more preferably above -0.030 and below 0.060, and further preferably above -0.020 and below 0.040.

[0038] In the present invention, the dimensional change rate H1 of the first protective film is calculated according to the following formula.

[0039] Dimensional change rate (H1) = (H1 48 -H10) / H1 48 ×100(i)

[0040] [Wherein, H1 48It refers to the dimension of the first protective film in a specified direction after the first protective film is left alone in an environment of 40°C and 60% relative humidity for 48 hours, and H10 refers to the initial dimension of the first protective film in a specified direction before leaving it alone in an environment of 40°C and 60% RH for 48 hours.]

[0041] Here, in the present invention, the initial size (H10) of the first protective film refers to the size of the first protective film, which is the object of determining the dimensional change rate, when it is left to stand for 168 hours in an environment of a temperature of 25°C and a relative humidity of 55%. By performing such a pretreatment, the occurrence of measurement errors caused by the storage conditions of the laminate and the protective film before measurement can be suppressed. In addition, H1 48 The "specified direction" when measuring the dimensions of H10 is the same as that of H11. For example, when the first protective film is cut and the initial dimension (H10) in the longitudinal direction is measured, the dimension (H10) in the longitudinal direction of the film is also measured after being left to stand at 40°C and 60% RH for 48 hours. 48 ), and the dimensional change rate is calculated. That is, the dimensional change rate H1 is obtained based on the initial size H10 and the size H1 obtained in the following measurements (1) and (2). 48 , a value calculated based on the above formula (i).

[0042] (1) After the first protective film for which the dimensional change rate is to be determined is left to stand for 168 hours in an environment of 25° C. and 55% RH, the dimension of the first protective film in a predetermined direction is measured as an initial dimension H10.

[0043] (2) Next, the first film having the initial dimensions measured was allowed to stand for 48 hours in an environment of 40° C. and 60% RH, and the dimension H1 in the same direction as the initial dimensions was measured. 48 .

[0044] The dimensional change rate H1 calculated in this way can be expressed as either a positive value (i.e., elongation or expansion) or a negative value (i.e., contraction). It should be noted that the dimensional change rate can be set as follows: the initial dimensions H10 of the film to be measured in different directions are measured, and after being placed under the above-mentioned specific storage conditions, the dimensions H1 in the same direction as the directions in which the initial dimensions are measured are measured. 48 , will be based on the initial size H10 and size H1 of the same direction 48 The value calculated based on the above formula (i) is averaged.

[0045] The size of the protective film can be measured using, for example, an image size measuring instrument, Nikon NEXIV (VMZ-R4540) or the like.

[0046] The dimensional change rate H2 of the second protective film and the dimensional change rate H3 of the third protective film can also be measured and calculated in the same manner as H1. It should be noted that in this case, in the method for measuring the dimensional change rate H1 of the first protective film and in formula (i), H1 is replaced by H2 or H3, H10 is replaced by H20 or H30, and H1 is replaced by H20 or H30. 48 Replace with H2 48 or H3 48 .

[0047] It should be noted that, in the present invention, as described later, a cured resin layer such as a hard coating layer or an optical functional layer capable of imparting various optical functions may be formed on the surface of the first to third protective films. When such a cured resin layer is directly formed on the surface of the protective film, the above-mentioned dimensional change rate is measured and calculated with respect to the cured resin layer and the protective film as a whole.

[0048] In the present invention, the dimensional change rate of each protective film is not particularly limited as long as it satisfies the relationship between the above-mentioned formula (1) and formula (2), but if the dimensional change rate of the protective film (in absolute value) becomes larger, it is difficult to control the relationship between the dimensional change rates of the three protective films. Therefore, in one embodiment of the present invention, the dimensional change rate H1 of the first protective film can be, for example, -0.3 to 0.1, preferably -0.2 to 0.05. In addition, the dimensional change rate H2 of the second protective film can be, for example, -0.1 to 0.3, preferably -0.05 to 0.2. In addition, the dimensional change rate H3 of the third protective film can be, for example, -0.1 to 0.3, preferably -0.05 to 0.2. In addition, if the dimensional change rate of each protective film is within the above range, it is also advantageous from the perspective of being able to suppress dimensional changes as a whole of the laminate during long-term storage.

[0049] In one embodiment of the present invention, the difference between the dimensional change rate H2 of the second protective film and the dimensional change rate H3 of the third protective film is preferably 0.1 or less, preferably 0.06 or less, and more preferably 0.03 or less in absolute value. If the second protective film and the third protective film show the same dimensional change behavior, there is a tendency that the positive curling suppression effect is improved.

[0050] The dimensional change rate of each protective film varies, for example, depending on the type of material constituting the protective film, the thickness of the protective film, the presence or absence of surface treatment of the protective film, moisture permeability, etc. That is, for example, by appropriately selecting and combining the type of material constituting the protective film, the thickness of the protective film, the presence or absence of surface treatment of the protective film, moisture permeability, etc., the dimensional change rate of the protective film can be controlled within the desired range. For example, in the case where the protective film is composed of a hydrophobic resin, such as a polyolefin resin such as a chain polyolefin resin and a cyclic polyolefin resin; a polyester resin such as polyethylene terephthalate, etc., the dimensional change rate tends to show a negative value (i.e., shrinkage). On the other hand, in the case where the protective film is composed of a hydrophilic resin, such as a cellulose resin such as triacetyl cellulose; a polymethyl methacrylate resin (PMMA), etc., the dimensional change rate tends to show a positive value (i.e., elongation or expansion). In addition, for example, if the thickness of the protective film increases, there is generally a tendency for the dimensional change rate to increase.

[0051] In the laminate of the present invention, the thickness (T2) of the second protective film and the thickness (T3) of the third protective film preferably satisfy the following formula (3):

[0052] 45≤ (T3 / T2) ×100≤350 (3).

[0053] If T2 and T3 are in a relationship that satisfies formula (3), the effect of suppressing the occurrence of positive curl over time is more excellent, and the effect of suppressing the mixing of bubbles when bonding to a display element, etc. can be further improved. The value of (T3 / T2)×100 is more preferably 80 or more, more preferably 100 or more, more preferably 300 or less, more preferably 250 or less, for example, 80 or more and 200 or less, or 80 or more and 190 or less.

[0054] In one embodiment of the present invention, the thickness of the third protective film is preferably 10 to 100 μm. If the thickness of the third protective film is within the above range, it is easy to control the value of (H3+H1)-H2 in formula (2) and the value of (T3 / T2)×100 in formula (3) to the desired range, which can improve the effect of suppressing the occurrence of positive curl over time. In addition, it is also advantageous in suppressing the occurrence of positive curl and being able to obtain a thin optical laminate. The thickness of the third protective film is preferably 10 to 100 μm, more preferably 10 to 60 μm, further preferably 10 to 40 μm, and particularly preferably 10 to 25 μm.

[0055] The thickness of the third protective film can be measured using a laser microscope, a film thickness meter, or the like. The same applies to the measurement of the thickness of each layer or film constituting the optical laminate, such as the first protective film and the second protective film.

[0056] In one embodiment of the present invention, the thickness of the first protective film is preferably 10 to 60 μm, more preferably 20 to 50 μm, and further preferably 25 to 40 μm. If the thickness of the first protective film is within the above range, the occurrence of positive curl over time can be effectively suppressed and the optical laminate can be made thinner.

[0057] The first protective film is preferably thinner than the third protective film. If the first protective film is thinner than the third protective film, it is easy to achieve a balance between thickness and dimensional change rate in the relationship with the second protective film located on the opposite side with the polarizer sandwiched therebetween, and it is easy to control the value of (H3+H1)-H2 in formula (2). As a result, it can be expected that the effect of suppressing the generation of positive curl over time will be further improved.

[0058] In one embodiment of the present invention, the thickness of the second protective film is preferably 5 to 60 μm, more preferably 20 to 50 μm, and further preferably 20 to 40 μm. If the thickness of the second protective film is within the above range, the occurrence of positive curl over time can be effectively suppressed and the optical laminate can be made thinner.

[0059] The thickness of the second protective film may be the same as or different from the thickness of the first protective film. In one embodiment of the present invention, the thickness of the first protective film is preferably the same as the thickness of the second protective film. The thickness of the first protective film and the second protective film being the same means that, for example, the difference in thickness between the two protective films is 15 μm or less, preferably 10 μm or less. If the thickness of the first protective film and the second protective film is the same, it is easy to achieve a balance between the thickness and dimensional change rate of each protective film located on both sides of the polarizer, and it is easy to control the value of (H3+H1)-H2 in formula (2). Thus, it is possible to further expect an improvement in the effect of suppressing the generation of positive curl over time.

[0060] Hereinafter, each structure of the optical layered body of the present invention will be described in detail.

[0061] (Protective film)

[0062] As the first protective film, the second protective film and the third protective film (hereinafter, when simply described as "protective film", all of the first protective film, the second protective film and the third protective film are taken as the object), for example, resin films that are conventionally known in the field of optical films can be used, and the material of each protective film can be appropriately selected in a manner that satisfies the relationship between the above formulas (1) and (2). As the resin constituting the protective film, for example, there can be mentioned chain or cyclic polyolefin resins such as polyethylene, polypropylene and norbornene polymers; cellulose resins such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; polyvinyl alcohol; polyester resins such as polyethylene terephthalate, polybutylene terephthalate and polyethylene naphthalate; (meth) acrylic resins selected from polymethyl methacrylate resins; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene ether, etc. Among them, from the viewpoint of strength and permeability, it is preferred to select the resin from cyclic polyolefin resin, cellulose resin and (meth) acrylic resin. They can be used alone or in combination of two or more. Such resin can be made into resin film by known methods such as solvent casting method and melt extrusion method. As protective film, cyclic polyolefin resin film, cellulose resin film and acrylic resin film are preferred.

[0063] Cyclic polyolefin resins are generally a general term for resins polymerized with cyclic olefins as polymerization units. Specifically, for example, ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers of chain olefins such as ethylene and propylene with cyclic olefins (representatively, random copolymers), and graft polymers obtained by modifying them with unsaturated carboxylic acids and their derivatives, and their hydrogenated products. Among them, norbornene resins using norbornene monomers such as norbornene and polycyclic norbornene monomers as cyclic olefins are preferred.

[0064] As the cyclic olefin resin film, a commercial product may be used. Examples of commercially available cyclic olefin resin films include "ESCENA" (registered trademark), "SCA40" (registered trademark) (all manufactured by Sekisui Chemical Co., Ltd.), "ZeonorFilm" (registered trademark) (manufactured by OPTEX Co., Ltd.), and "ArtonFilm" (registered trademark) (manufactured by JSR Co., Ltd.).

[0065] The cellulose resin is preferably a cellulose ester resin, which is usually an ester of cellulose and a fatty acid. Specific examples of the cellulose ester resin include triacetyl cellulose, diacetyl cellulose, cellulose tripropionate, cellulose dipropionate, etc. In addition, substances obtained by copolymerizing these substances and substances obtained by modifying a portion of the hydroxyl groups with other substituents may also be used. Among them, triacetyl cellulose (TAC) is preferred.

[0066] As the cellulose resin film, commercial products may be used. Examples of commercially available cellulose resin films include "FUJITAC Film" (manufactured by Fujifilm Corporation), "KC8UX2M", "KC8UY" and "KC4UY" (manufactured by Konica Minolta, Inc.).

[0067] As the (meth)acrylic resin, for example, homopolymers of alkyl methacrylate or alkyl acrylate, copolymers of alkyl methacrylate and alkyl acrylate, etc. can be mentioned. As the alkyl methacrylate, specifically, methyl methacrylate, ethyl methacrylate, propyl methacrylate, etc. can be mentioned. In addition, as the alkyl acrylate, specifically, methyl acrylate, ethyl acrylate, propyl acrylate, etc. can be mentioned. As these (meth)acrylic resins, resins commercially available as general-purpose (meth)acrylic resins can be used. As the (meth)acrylic resin, it is further preferred to be a polymer of a monofunctional acrylic monomer, preferably showing a glass transition temperature below 25°C, more preferably below 0°C. As such a (meth)acrylic resin, for example, polymethyl methacrylate can be mentioned.

[0068] In one embodiment of the present invention, as the first protective film, a resin film composed of a resin having a tendency that the dimensional change rate H1 does not change or shows a negative value (i.e., shrinkage) is preferably used. Examples of such a resin film include polyolefin resin films, polyester resin films, etc. Among them, cyclic polyolefin resin films are preferred.

[0069] In one embodiment of the present invention, as the second protective film, a resin film composed of a resin having a tendency that the dimensional change rate H2 shows a positive value (i.e., elongation or expansion) is preferably used. As such a resin film, for example, a cellulose resin film, a (meth) acrylic resin film, etc. can be cited. Among them, a cellulose resin film is preferred, and a triacetyl cellulose film is particularly preferred.

[0070] In one embodiment of the present invention, as the third protective film, a resin film composed of a resin having a tendency that the dimensional change rate H3 shows a positive value (i.e., elongation or expansion) is preferably used. As such a resin film, for example, a cellulose resin film, a (meth) acrylic resin film, etc. can be cited. Among them, a cellulose resin film or a (meth) acrylic resin film is preferred, and a triacetyl cellulose film or a polymethyl methacrylate polymer film is preferred.

[0071] In the present invention, the combination of the first protective film, the second protective film and the third protective film can be appropriately determined in a manner that the dimensional change rate of each protective film satisfies the relationship between the above-mentioned formula (1) and formula (2). The first protective film, the second protective film and the third protective film may be the same as or different from each other. In the case where the first protective film is a resin film formed of a resin different from the second protective film and / or the third protective film, it is originally a structure that is prone to positive curling, but the effect of suppressing the positive curling can be obtained, and there is a tendency that the effect of the present invention becomes significant. In addition, from the viewpoint of easy control of curling, the first protective film or the second protective film and the third protective film are preferably films formed of the same resin.

[0072] As a combination that can easily control the dimensional change rate of each protective film to the relationship shown in formula (1) and formula (2) and can be expected to suppress the occurrence of positive curl over time, for example, the following combination can be cited. It should be noted that the following combination shows the stacking order of the third protective film / the first protective film / the second protective film.

[0073] Cellulose resin film / cyclic polyolefin resin film (hereinafter referred to as COP) / cellulose resin film, (meth)acrylic resin film / COP / cellulose resin film, more preferably triacetyl cellulose film (hereinafter referred to as TAC) / COP / TAC, polymethyl methacrylate resin (hereinafter referred to as PMMA) / COP / TAC.

[0074] In order to impart adhesion to the surface of the protective film, the film surface may be modified by corona treatment, plasma treatment, flame treatment, etc., depending on the structure of the adjacent layers, etc. In addition, hard coating treatment, antireflection treatment, antistatic treatment, etc. may also be performed.

[0075] In the present invention, the third protective film is usually assembled into an image display device, etc. as a constituent member of the optical stack in a state where it is not peeled off from the optical stack. For example, a protective film provided to temporarily protect a polarizing plate, etc. before assembling the optical stack into a display device is stacked in a manner that can eventually be peeled off from the optical stack. For such a film that can be peeled off, it may be difficult to ensure sufficient support for suppressing the deformation (positive curling) of the optical stack in the relationship with the first protective film and the second protective film. Therefore, the third protective film is preferably stacked with a certain or more adhesion force via the second adhesive adhesive layer in a manner that is not peeled off from other components such as the polarizing plate constituting the optical stack. In one embodiment of the present invention, the peeling force when peeling off the protective film from the optical stack is preferably 1N / 25mm or more. The upper limit is not particularly limited, and it can be firmly attached to the extent that material damage occurs when it is desired to be peeled off, that is, the optical stack, the third protective film or the second adhesive adhesive layer is destroyed. When the peeling force of the third protective film is not less than the above lower limit, peeling from the optical laminate can be suppressed, and the third protective film can fully function in preventing positive curling.

[0076] The peeling strength of the third protective film is a layer (for example, a layer between the third protective film and the second adhesive layer) of the optical laminate to be measured. Figure 1 The value measured by the peeling force required to peel off the third protective film (the first protective film in the middle). For example, for a test piece in which the surface of the optical laminated body opposite to the third protective film for measuring the peeling force (for example, the side of the phase difference film opposite to the first adhesive layer) is fixed to a glass plate or the like by an adhesive, the peeling force required to peel off the third protective film for measuring the peeling force from the optical laminated body of the test piece is measured. When peeling off the third protective film, its peeling surface may be between the third protective film and the second adhesive layer, or between the layer to which the third protective film is bonded via the second adhesive layer and the second adhesive layer. The above-mentioned peeling force can be measured according to the 90° peeling test method specified in JIS K 6854-1:1999.

[0077] The peeling force of the third protective film can be controlled, for example, by the type and thickness of the third protective film, the surface treatment state, the composition and thickness of the layer laminated with the third protective film via the second adhesive layer, the surface treatment state, the type of the second adhesive layer, its thickness, etc.

[0078] When assembled in a display device, the third protective film located on the observation side may be a protective film that performs functions for image display (display screen, etc.) (for example, to improve the ease of image observation), and may have optical functions such as phase difference function (1 / 4 wavelength plate, etc.), brightness improvement function, anti-glare function, anti-reflection function, diffusion function, and light focusing function. In this case, the third protective film itself may have such optical functions in a single layer, or may be a multilayer structure in which an optical functional layer having various optical functions is formed on the resin film as described above.

[0079] In one embodiment of the present invention, from the viewpoint of being able to obtain the functions of preventing surface damage and adjusting the dimensional change rate, the optical laminate of the present invention preferably also has a cured resin layer on the side of the third protective film opposite to the circular polarizer. The above-mentioned cured resin layer can be, for example, a hard coating layer located at the outermost layer of the optical laminate for protecting and strengthening the optical laminate, or a layer having the above-mentioned various optical functions (such as an anti-glare layer, an anti-reflection layer). In the case where the optical laminate includes the above-mentioned cured resin layer, the thickness of the cured resin layer is preferably 0.5 to 10 μm, more preferably 1 to 5 μm, and further preferably 2 μm to 5 μm. If the thickness of the cured resin layer is within the above-mentioned range, the function that the third protective film can perform is not affected in the present invention, and not only the desired function brought by the cured resin layer can be exerted, but also the dimensional change of the third protective film can be adjusted, so it is easy to achieve accurate curling control in the present invention.

[0080] (Polyvinyl alcohol polarizing film)

[0081] The polyvinyl alcohol-based polarizing film constituting the optical laminate of the present invention is a film having a polarizing function. Such a polarizing film is typically a stretched film adsorbed with a dichroic dye having absorption anisotropy, and can be produced, for example, through the following steps: a step of uniaxially stretching a polyvinyl alcohol-based resin film; a step of dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye; a step of treating the polyvinyl alcohol-based resin film adsorbed with the dichroic dye with a boric acid aqueous solution; and a step of washing with water after the treatment with the boric acid aqueous solution.

[0082] The polyvinyl alcohol resin is obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be exemplified. As other monomers copolymerizable with vinyl acetate, for example, unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, acrylamides having an ammonium group, etc. can be cited.

[0083] The saponification degree of the polyvinyl alcohol resin is generally about 85 to 100 mol%, preferably 90 mol% or more, and more preferably 98 mol% or more. The polyvinyl alcohol resin may be a partially modified polyvinyl alcohol, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes may also be used. The degree of polymerization of the polyvinyl alcohol resin is generally about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.

[0084] The film obtained by forming such a polyvinyl alcohol-based resin into a film is used as a raw material film of a polarizing film. The method of forming a polyvinyl alcohol-based resin into a film is not particularly limited, and the film can be formed by a known method. The film thickness of the polyvinyl alcohol-based raw material film can be set to about 10 to 150 μm, for example.

[0085] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before dyeing with a dichroic pigment, or it can be performed simultaneously with dyeing or after dyeing. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before boric acid treatment or during boric acid treatment. In addition, uniaxial stretching can also be performed in these multiple stages. During uniaxial stretching, uniaxial stretching can be performed between rollers with different peripheral speeds, or uniaxial stretching can be performed using a hot roller. In addition, uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen using a solvent. The stretching ratio is usually about 3 to 8 times.

[0086] The polyvinyl alcohol-based resin film is dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.

[0087] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As dichroic organic dyes, dichroic direct dyes containing diazo compounds such as CIDIRECT RED 39 and dichroic direct dyes containing compounds such as triazo and tetrakis azo can be cited. The polyvinyl alcohol-based resin film is preferably immersed in water before dyeing.

[0088] When iodine is used as a dichroic pigment, a method of dyeing by immersing a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide is generally adopted. The content of iodine in the aqueous solution is generally about 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is generally about 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used in dyeing is generally about 20 to 40°C. In addition, the immersion time (dyeing time) in the aqueous solution is generally about 20 to 1,800 seconds.

[0089] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye is generally adopted. The content of the dichroic organic dye in the aqueous solution is generally 1×10 -4 ~10 parts by mass, preferably 1×10 -3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is usually about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 10 to 1,800 seconds.

[0090] The boric acid treatment after dyeing with a dichroic pigment can usually be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous boric acid solution. The content of boric acid in the aqueous boric acid solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. When iodine is used as the dichroic pigment, the aqueous boric acid solution preferably contains potassium iodide, and the content of potassium iodide at this time is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous boric acid solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0091] The polyvinyl alcohol-based resin film after the boric acid treatment is usually subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of the water in the water washing treatment is usually about 5 to 40° C. In addition, the immersion time is usually about 1 to 120 seconds.

[0092] After washing with water, a drying process is performed to obtain a polarizer. The drying process can be performed using, for example, a hot air dryer or a far-infrared heater. The temperature of the drying process is usually about 30 to 100° C., preferably 50 to 80° C. The time of the drying process is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying, the moisture content of the polarizing film is reduced to a practical level. The moisture content is usually about 5 to 20% by mass, preferably 8 to 15% by mass. If the moisture content is within the above range, a polarizing film with moderate flexibility and excellent thermal stability can be obtained.

[0093] In the present invention, the thickness of the polarizing film is preferably 5 to 40 μm, more preferably 5 to 30 μm, further preferably 5 to 20 μm, and particularly preferably 5 to 15 μm.

[0094] (First Adhesive Layer and Second Adhesive Layer)

[0095] In the optical laminate of the present invention, the first protective film is laminated via the first adhesive layer on one side of the polarizing film, and the second protective film is laminated via the second adhesive layer on the other side of the polarizing film. These layers are stacked adjacent to each other to form a laminate that functions as a polarizing plate. The first adhesive layer and the second adhesive layer (hereinafter, when only recorded as "adhesive layer", the first adhesive layer and the second adhesive layer are the objects) are layers formed by adhesives. As long as the adhesive layer can function as a layer for laminating the polarizing film to the protective film, it can be formed by a known adhesive. As such an adhesive, a conventionally known adhesive can be used without particular restriction, and can be appropriately selected according to the type of the laminating protective film, the characteristics and uses required by the optical laminate. As an adhesive that can form the first adhesive layer and the second adhesive layer, for example, active energy ray-curable adhesives, water-based adhesives, organic solvent-based adhesives and solvent-free adhesives can be cited. Among them, water-based adhesives or active energy ray-curable adhesives are preferred.

[0096] As the water-based adhesive, for example, polyvinyl alcohol-based resin or urethane resin is used as a main component, and a crosslinking agent or curable compound such as an isocyanate-based compound or epoxy compound is usually blended into a composition to improve adhesiveness.

[0097] When using a polyvinyl alcohol resin as the main component of the water-based adhesive, in addition to partially saponified polyvinyl alcohol and completely saponified polyvinyl alcohol, a modified polyvinyl alcohol resin such as carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol and amino-modified polyvinyl alcohol can also be used. An aqueous solution of such a polyvinyl alcohol resin is used as a water-based adhesive. The concentration of the polyvinyl alcohol resin in the water-based adhesive is usually 1 to 10 parts by mass, preferably 1 to 5 parts by mass, relative to 100 parts by mass of water.

[0098] In the water-based adhesive containing the aqueous solution of the polyvinyl alcohol resin, in order to improve the adhesiveness, a curable compound such as a polyaldehyde, a water-soluble epoxy resin, a melamine compound, a zirconium oxide compound, and a zinc compound can be mixed. As a water-soluble epoxy resin, there is a water-soluble polyamide epoxy resin obtained by reacting polyamide polyamine with epichlorohydrin, and the polyamide polyamine is obtained by reacting a polyalkylene polyamine such as diethylenetriamine and triethylenetetramine with a dicarboxylic acid such as adipic acid. As a commercial product of such a polyamide epoxy resin, for example, there are "Sumirez Resin 650" and "Sumirez Resin 675" sold by Sumika Chemtex Co., Ltd., and "WS-525" sold by Japan PMC Co., Ltd., etc. In the case of mixing a water-soluble epoxy resin, its addition amount is usually about 1 to 100 parts by mass relative to 100 parts by mass of the polyvinyl alcohol resin, preferably 1 to 50 parts by mass.

[0099] In addition, when using carbamate resin as the main component of water-based adhesive, it is effective to use polyester ionomer carbamate resin as the main component of water-based adhesive. The polyester ionomer carbamate resin mentioned here refers to a carbamate resin having a polyester skeleton, into which a small amount of ionic components (hydrophilic components) are introduced. The ionomer carbamate resin is directly emulsified in water without using an emulsifier to form an emulsion, so it can be made into a water-based adhesive. When using polyester ionomer carbamate resin, it is effective to use a water-soluble epoxy compound as a crosslinking agent.

[0100] The components constituting the water-based adhesive are usually used in a state of being dissolved in water. The adhesive layer can be obtained by applying the water-based adhesive on the surface to be formed into the adhesive layer and drying it. The components that are insoluble in water can be dispersed in the system.

[0101] As a method for forming an adhesive layer on a polarizing film by a water-based adhesive, there can be cited a method of directly applying the above-mentioned adhesive composition on the surface of the polarizing film and drying it. The thickness of the above-mentioned adhesive layer is usually about 0.001 to 5 μm, preferably more than 0.01 μm, and preferably less than 2 μm, and more preferably less than 1 μm. If the adhesive layer is within the above range, the necessary adhesion can be ensured without affecting the positive curl suppression effect obtained by controlling the dimensional change rate of each protective film, the optical properties and / or appearance of the polarizing plate, etc.

[0102] Active energy ray-curable adhesives are adhesives that are cured by irradiation with active energy rays such as ultraviolet rays. Examples of active energy ray-curable adhesives include cationically polymerizable adhesives containing epoxy compounds and cationic polymerization initiators; free radically polymerizable adhesives containing acrylic curing components and free radical polymerization initiators; adhesives containing both cationically polymerizable curing components such as epoxy compounds and free radically polymerizable curing components such as acrylic compounds, and further containing cationic polymerization initiators and free radical polymerization initiators; and adhesives that are cured by irradiation with electron beams without containing these polymerization initiators.

[0103] Among them, free radical polymerizable active energy ray-curable adhesives containing acrylic curing components and photo-free radical polymerization initiators, and cationic polymerizable active energy ray-curable adhesives containing epoxy compounds and photo-cationic polymerization initiators are preferred. As acrylic curing components, (meth)acrylates such as methyl (meth)acrylate and hydroxyethyl (meth)acrylate and (meth)acrylic acid can be cited. The active energy ray-curable adhesive containing epoxy compounds can further contain compounds other than epoxy compounds. As compounds other than epoxy compounds, oxetane compounds, acrylic compounds, etc. can be cited.

[0104] As the photoradical polymerization initiator and the cationic polymerization initiator, any initiator known in the field of active energy ray-curable adhesives can be appropriately selected and used. The content of the photoradical polymerization initiator and the cationic polymerization initiator is usually 0.5 to 20 parts by mass, preferably 1 to 15 parts by mass, relative to 100 parts by mass of the active energy ray-curable adhesive.

[0105] As a method for forming an adhesive layer on a polarizing film by an active energy ray-curable adhesive, there can be cited a method of applying the above-mentioned adhesive composition on the surface of the polarizing film, drying the solvent as needed, and irradiating active energy rays to form an adhesive layer. The thickness of the above-mentioned adhesive layer is usually about 0.001 to 5 μm, preferably more than 0.01 μm, and preferably less than 2 μm, and more preferably less than 1 μm. If the adhesive layer is within the above range, the necessary adhesion can be ensured without affecting the positive curl suppression effect obtained by controlling the dimensional change rate of each protective film, the optical properties and / or appearance of the polarizing plate, etc.

[0106] In the optical layered body of the present invention, the first adhesive layer and the second adhesive layer may be the same or different in terms of composition, thickness, etc.

[0107] (First Adhesive Layer and Second Adhesive Layer)

[0108] In the optical laminate of the present invention, a phase difference film is laminated via the first adhesive layer on the surface of the second protective film on the opposite side of the polarizing film. The layers from the first protective film to the phase difference film are laminated in a mutually adjacent manner to form a laminate that functions as a circular polarizing plate. In addition, a third protective film is laminated via the second adhesive layer on the first protective film side of the circular polarizing plate. The first adhesive layer and the second adhesive layer (hereinafter, in the case of being abbreviated as "adhesive layer", the first adhesive layer and the second adhesive layer are the objects) are layers formed by an adhesive (referring to an adhesive, an adhesive, or an agent having these characteristics). As long as the adhesive layer can function as a layer for bonding the third protective film to the circular polarizing plate and bonding the second protective film to the phase difference film, it can be formed by a known adhesive. As such a tackiness adhesive, any conventionally known tackiness adhesive can be used without particular limitation, and can be appropriately selected according to the type of protective film, retardation film, etc. to be bonded, and the properties and application required of the optical laminate.

[0109] As the adhesive adhesive capable of forming the first adhesive layer and the second adhesive layer, for example, the adhesive described above as the adhesive capable of forming the first adhesive layer, the adhesive with resins such as (meth) acrylic acid, rubber, urethane, ester, silicone, and polyvinyl ether as the main component can be cited. The adhesive can be an active energy ray-curable adhesive, a thermosetting adhesive, etc. As the adhesive adhesive capable of forming the first adhesive layer and the second adhesive layer, an adhesive is preferably used, wherein an adhesive with excellent transparency, weather resistance, heat resistance, etc., based on a (meth) acrylic resin polymer.

[0110] The (meth)acrylic resin (base polymer) used in the adhesive may be, for example, a polymer or copolymer having one or more of (meth)acrylic acid esters such as butyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate as monomer components. In addition, the (meth)acrylic resin may be a resin obtained by copolymerizing a polar monomer. As the polar monomer, for example, monomers having a carboxylic acid group, a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate may be cited.

[0111] In one embodiment of the present invention, the structural unit derived from (meth) acrylic acid ester in the (meth) acrylic resin constituting the adhesive is preferably 80 to 100% by mass, more preferably 85% by mass or more, and further preferably 90% by mass or more, relative to the total mass of all structural units constituting the (meth) acrylic resin. In addition, when the (meth) acrylic resin contains structural units derived from polar monomers, the structural unit derived from the polar monomer is preferably 0.1 to 10% by mass, more preferably 0.5% by mass or more, further preferably 1% by mass or more, and further, more preferably 8% by mass or less, relative to the total mass of all structural units constituting the (meth) acrylic resin.

[0112] The weight average molecular weight (hereinafter, also referred to as "Mw") of the (meth) acrylic resin is preferably 500,000 to 2.5 million. If the weight average molecular weight is 500,000 or more, the durability of the first adhesive layer under high temperature and high humidity environments can be improved. If the weight average molecular weight is 2.5 million or less, the handling property when applying the adhesive becomes good. The molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter, also referred to as "Mn") is usually 2 to 10. In this specification, the weight average molecular weight and the number average molecular weight are polystyrene conversion values ​​measured by gel permeation chromatography (GPC).

[0113] The adhesive may contain only the acrylic resin or a crosslinking agent in combination. Examples of the crosslinking agent include a crosslinking agent that is a metal ion with a valence of more than two and forms a carboxylic acid metal salt with a carboxyl group; a crosslinking agent that is a polyamine compound and forms an amide bond with a carboxyl group; a crosslinking agent that is a polyepoxide compound or a polyol and forms an ester bond with a carboxyl group; and a crosslinking agent that is a polyisocyanate compound and forms an amide bond with a carboxyl group. Among them, polyisocyanate compounds are preferred from the viewpoints of crosslinking speed, durability, etc.

[0114] When the cross-linking agent is contained, the ratio thereof is, for example, 0.01 to 10 parts by mass, preferably 0.1 to 3 parts by mass, and more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the base polymer.

[0115] Adhesive can further include silane compounds as needed.By containing silane compounds, it is possible to improve the adhesion of the adhesive layer formed by the adhesive and the layer stacked.As silane compounds, for example, vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tris (2-methoxyethoxy) silane, 3-glycidoxy propyl trimethoxy silane, 3-glycidoxy propyl triethoxy silane, 3-glycidoxy propyl methyl dimethoxy silane, 3-glycidoxy propyl ethoxy dimethyl silane, 2- (3,4-epoxycyclohexyl) ethyl trimethoxy silane, 3-chloropropyl methyl dimethoxy silane, 3-chloropropyl trimethoxy silane, 3-methacryloxy propyl trimethoxy silane, 3-mercaptopropyl trimethoxy silane etc. can be enumerated.They can be used alone, and two or more kinds can also be used in combination.

[0116] When the silane compound is contained, the content in the adhesive is usually 0.01 to 10 parts by mass, preferably 0.03 to 5 parts by mass, more preferably 0.05 to 2 parts by mass, and further preferably 0.1 to 1 part by mass, based on 100 parts by mass of the base polymer.

[0117] In this specification, an active energy ray-curable adhesive refers to an adhesive that has the property of being cured by irradiation with active energy rays such as ultraviolet rays and electron beams, has adhesive properties before irradiation with active energy rays and can be closely attached to an adherend such as a film, and has the property of being cured by irradiation with active energy rays and being able to adjust the adhesion, etc. The active energy ray-curable adhesive is preferably an ultraviolet-curable adhesive.

[0118] The active energy ray-curable adhesive generally contains an energy ray-polymerizable compound in addition to the above-mentioned base polymer such as a (meth)acrylic resin and a crosslinking agent, and may contain a photopolymerization initiator, a photosensitizer, etc. as necessary.

[0119] Examples of active energy ray-polymerizable compounds include (meth)acrylic compounds such as (meth)acrylic acid ester monomers having at least one (meth)acrylic acid ester group in the molecule; (meth)acrylic acid ester oligomers having at least two (meth)acrylic acid ester groups in the molecule obtained by reacting two or more functional group-containing compounds; and (meth)acrylic acid-containing compounds.

[0120] The adhesive may further include conventional components as components constituting the adhesive. Such components include, for example, additives such as resins other than the base polymer, tackifiers, fillers (metal powders, other inorganic powders, etc.), antioxidants, ultraviolet absorbers, dyes, pigments, colorants, defoamers, and anticorrosives.

[0121] In one embodiment of the present invention, the first adhesive layer and the second adhesive layer may be formed by a reaction product of an adhesive comprising a base polymer such as a (meth) acrylic resin, a crosslinking agent, and a silane compound. Such an adhesive layer may be formed by applying a diluent of an adhesive comprising the above components, such as an organic solvent, to the surface on which the adhesive layer is to be formed and drying it.

[0122] In addition, in one embodiment of the present invention, the first adhesive layer and the second adhesive layer may be layers formed of an active energy ray-curable adhesive. When the adhesive layer is formed of an active energy ray-curable adhesive, for example, an organic solvent-diluted liquid of an adhesive composed of the above-mentioned components is applied to the surface where the adhesive layer is formed and dried, and the formed adhesive layer is irradiated with active energy rays, thereby forming a cured layer having a desired degree of curing.

[0123] The first tackiness adhesive layer and the second tackiness adhesive layer may be the same or different in terms of composition, thickness, structure, and the like.

[0124] The thickness of the first adhesive layer can be appropriately determined according to the composition of the adhesive, the structure and size of the optical laminate, etc. In one embodiment of the present invention, the thickness of the first adhesive layer is usually 1 to 30 μm, preferably 5 to 25 μm, and more preferably 5 to 20 μm. If the thickness of the first adhesive layer is within the above range, the phase difference film can be bonded with high adhesion, and a thin laminate structure with excellent effect of suppressing the occurrence of positive curling over time can be formed.

[0125] The thickness of the second adhesive layer can be appropriately determined according to the composition of the adhesive, the structure and size of the optical laminate, etc. In one embodiment of the present invention, the thickness of the second adhesive layer is preferably 1 to 50 μm, more preferably 3 to 25 μm, and further preferably 5 to 15 μm. If the thickness of the second adhesive layer is within the above range, the third protective film can be adhered to the first protective film side of the polarizing plate with high adhesion, and a laminate structure with excellent effect of suppressing the occurrence of positive curling over time can be formed.

[0126] The water vapor permeability of the first adhesive layer and the second adhesive layer at a temperature of 40° C. and a relative humidity of 90% is preferably 1,000 to 10,000 g / m 2 24h, more preferably 2,000 to 9,000 g / m 2·24h. If the water vapor permeability of the adhesive layer is within the above range, deformation is less likely to occur even in a high temperature and high humidity environment, and the effect of suppressing the occurrence of positive curling over time can be improved. The water vapor permeability of the adhesive layer can be controlled to a desired range by the composition and thickness of the adhesive forming the adhesive layer.

[0127] The water vapor permeability of the adhesive layer can be measured using a water vapor permeability meter. If it is difficult to measure the water vapor permeability of the adhesive layer alone, the water vapor permeability can be calculated from the ratio of the adhesive layer to the highly permeable substrate after bonding the adhesive to the highly permeable substrate.

[0128] In the optical laminate of the present invention, the storage modulus of the first adhesive layer and the second adhesive layer is preferably 0.01MPa or more, more preferably 0.05MPa or more, particularly preferably 0.07MPa or more, preferably 0.5MPa or less, more preferably 0.2MPa or less, particularly preferably 0.15MPa or less. If the storage modulus of the adhesive layer is within the above range, it is not easy to produce the offset between the layers pasted by the adhesive layer, and the effect of suppressing the occurrence of positive curling can be improved. The storage modulus of the adhesive layer can be controlled to the desired range by the composition of the adhesive layer forming the adhesive layer. In the adhesive layer formed by the active energy ray curing adhesive, the storage modulus can be mostly improved.

[0129] The storage modulus of the adhesive layer can be measured using a viscoelasticity measuring device. Specifically, for example, it can be measured by the method described in the examples described below.

[0130] The glass transition temperature (Tg) of the first adhesive layer and the second adhesive layer is preferably below room temperature (25°C), more preferably below 0°C, and usually above -40°C. If the glass transition temperature of the adhesive layer is within the above range, sufficient adhesive force can be exerted. The glass transition temperature of the adhesive layer can be controlled to a desired range according to the type, amount, and combination of the base polymer contained in the adhesive forming the adhesive layer, the type, amount, and combination of the monomers used to form the polymer.

[0131] The glass transition temperature of the adhesive layer can be measured by the method described in Examples described below, for example.

[0132] (Phase difference film)

[0133] In the optical laminate of the present invention, the phase difference film stacked adjacent to the first adhesive layer is formed by a polymer of a polymerizable liquid crystal compound. If the phase difference film attached to the polarizing plate via the first adhesive layer is a cured layer (cured film) of a polymerizable liquid crystal compound, a thin circular polarizing plate can be formed compared to the case where the layer with a phase difference is formed by a stretched film, but since the phase difference film is a thin film (e.g., 5 μm or less), positive curling over time is prone to occur. In the optical laminate of the present invention, by providing a third protective film on the surface of the circular polarizing plate opposite to the phase difference film, the third dimensional change rate is controlled in the relationship with the first protective film and the second protective film, and the positive curling that is originally easy to occur due to the use of a thin film phase difference film can be effectively suppressed.

[0134] From the viewpoint that the above-mentioned effect is easy to become significant, in one embodiment of the present invention, the thickness of the phase difference film stacked adjacent to the first adhesive layer is 0.5 to 5 μm, preferably 0.5 to 3.0 μm, and more preferably 1.0 to 3.0 μm. It should be noted that in the present invention, the phase difference film is a film that shows a phase difference in the plane or thickness direction, and can be a separate layer formed by a polymer of a polymerizable liquid crystal compound, or when the layer formed by the polymer exists adjacent to the orientation film used to form it, the orientation film can be included. In the case where the phase difference film includes an orientation film, a thickness of 0.1 μm to 5 μm is further added.

[0135] In this specification, the phase difference film may be one or may include more than two. In the case of including more than two phase difference films, the thickness of each phase difference film can be appropriately determined according to the optical properties required by each phase difference film, the composition of the optical laminate, the purpose, etc., and the thickness may be the same as or different from each other. Hereinafter, in the case where the optical laminate includes more than two phase difference films, a film formed by laminating a plurality of phase difference films via an adhesive layer is sometimes referred to as a composite phase difference film. As a composite phase difference film, that is, the total thickness of two or more phase difference films and the adhesive layer between them, it is preferably 15 μm or less, more preferably 10 μm or less, further preferably 8 μm or less, and particularly preferably 6 μm or less.

[0136] In order for the optical layered body of the present invention to function as a circularly polarizing plate, the optical layered body preferably includes a retardation film satisfying the following formula (4).

[0137] 120nm≤Re(550)≤170nm (4)

[0138] [Wherein, Re(λ) represents the in-plane retardation value of the retardation film at a wavelength of λ nm]

[0139] That is, when the optical layered body of the present invention includes only one retardation film, the retardation film preferably satisfies the above formula (4).

[0140] If the in-plane phase difference Re (550) of the phase difference film is within the range of formula (4), the phase difference film becomes a phase difference film that functions as a quarter wavelength plate, and the effect of improving the front reflection hue (effect of suppressing coloration) when the optical laminate (circular polarizing plate) containing the phase difference film is applied to an organic EL display device, etc. is easily improved. A further preferred range of the in-plane phase difference value is 130nm≤Re (550)≤150nm.

[0141] In addition, the above-mentioned retardation film preferably satisfies the following formula (5) and formula (6) in addition to formula (4):

[0142] Re(450) / Re(550)≤1.00 (5)

[0143] 1.00≤Re(650) / Re(550) (6)

[0144] [wherein, Re(λ) represents the in-plane retardation value of the retardation film at a wavelength of λ nm].

[0145] When the phase difference film satisfies formula (5) and formula (6), the phase difference film shows that the in-plane phase difference value at a short wavelength is less than the in-plane phase difference value at a long wavelength, so-called reverse wavelength dispersion. The optical laminate (circular polarizing plate) having such a phase difference film has a tendency to have excellent front hue when assembled in an organic EL display device, etc. From the viewpoint of improving the reverse wavelength dispersion and further improving the effect of improving the reflected hue in the front direction, Re (450) / Re (550) is preferably 0.70 or more, more preferably 0.78 or more, and preferably 0.92 or less, more preferably 0.90 or less, more preferably 0.87 or less, particularly preferably 0.86 or less, and more particularly preferably 0.85 or less. In addition, Re (650) / Re (550) is preferably 1.01 or more, more preferably 1.02 or more.

[0146] The above-mentioned in-plane phase difference value can be adjusted by the film thickness dA of the phase difference film. The in-plane phase difference value is determined by the formula ReA(λ) = (nxA(λ)-nyA(λ)) × dA [where nxA(λ) represents the main refractive index at a wavelength λnm in the plane of the phase difference film, nyA(λ) represents the refractive index at a wavelength λnm in the direction orthogonal to the direction of nxA in the same plane as nxA, and dA represents the film thickness of the phase difference film]. Therefore, in order to obtain the desired in-plane phase difference value (ReA(λ): in-plane phase difference value of the phase difference film at a wavelength λ (nm)), it is sufficient to adjust the three-dimensional refractive index and the film thickness dA.

[0147] The optical laminate of the present invention preferably includes a phase difference film formed by curing a polymerizable liquid crystal compound in a state of being oriented in a horizontal direction relative to the plane of the phase difference film. In the case where the optical laminate of the present invention includes only one phase difference film, the phase difference film is usually a "horizontally oriented liquid crystal cured film" and preferably satisfies the above formulas (4) to (6).

[0148] The optical laminate of the present invention may include a phase difference film as a positive C plate (nx≈ny<nz) in addition to a phase difference film having a 1 / 4 wavelength plate function. The phase difference film as a positive C plate is a "vertically oriented liquid crystal cured film" formed by curing a polymerizable liquid crystal compound in a state of being oriented in a vertical direction relative to the plane of the phase difference film. By combining a phase difference film having a 1 / 4 wavelength plate function and a phase difference film as a positive C plate, when the optical laminate is applied to an organic EL display device, etc., in addition to improving the front reflection color tone, it is also possible to expect an improvement in the oblique reflection color tone.

[0149] When the optical laminate of the present invention includes a retardation film as a positive C plate, the retardation film (hereinafter also referred to as a "vertically aligned liquid crystal cured film") preferably satisfies the formulas (7) to (9).

[0150] Rth(450) / Rth(550)≤1.00 (7)

[0151] 1.00≤Rth(650) / Rth(550) (8)

[0152] -100nm≤Rth(550)≤-40nm (9)

[0153] [In the formula, Rth(λ) represents the phase difference value in the thickness direction of the vertically aligned liquid crystal curing film at a wavelength of λnm, RthC = ((nxC(λ)+nyC(λ)) / 2-nzC)×dC (In the formula, dC represents the thickness of the vertically aligned liquid crystal curing film, nxC represents the principal refractive index at a wavelength of λnm in a direction parallel to the plane of the vertically aligned liquid crystal curing film in the refractive index ellipsoid formed by the vertically aligned liquid crystal curing film, nyC represents the refractive index at a wavelength of λnm in a direction parallel to the plane of the vertically aligned liquid crystal curing film and orthogonal to the direction of the above nxC in the refractive index ellipsoid formed by the vertically aligned liquid crystal curing film, and nzC represents the refractive index at a wavelength of λnm in a direction perpendicular to the plane of the vertically aligned liquid crystal curing film in the refractive index ellipsoid formed by the vertically aligned liquid crystal curing film).]

[0154] When the vertically oriented liquid crystal curing film satisfies formulas (7) and (8), for a circularly polarizing plate including the phase difference film (vertically oriented liquid crystal curing film), the decrease in ellipticity can be suppressed on the short wavelength side, and the oblique reflection hue can be improved. The value of Rth(450) / Rth(550) in the vertically oriented liquid crystal curing film is preferably 0.70 or more, more preferably 0.78 or more, and preferably 0.92 or less, more preferably 0.90 or less, further preferably 0.87 or less, particularly preferably 0.86 or less, and more particularly preferably 0.85 or less. In addition, Rth(650) / Rth(550) is preferably 1.01 or more, more preferably 1.02 or more.

[0155] In addition, when the retardation film as a positive C plate satisfies formula (9), the oblique reflection hue can be improved when the optical laminate (circular polarizing plate) containing the retardation film is applied to an organic EL display device. The retardation value Rth (550) in the film thickness direction of the retardation film (vertically aligned liquid crystal cured film) is more preferably greater than -90 nm, further preferably greater than -80 nm, and more preferably less than -50 nm.

[0156] The optical laminate of the present invention may further include a phase difference film having a 1 / 2 wavelength plate function in addition to a phase difference film having a 1 / 4 wavelength plate function. As the phase difference film that functions as a 1 / 4 wavelength plate at this time, a phase difference film that satisfies the following formula (10), formula (12) and formula (13) can be cited. In addition, regarding the phase difference film that functions as a 1 / 2 wavelength plate, a phase difference film that satisfies the following formula (11), formula (12) and formula (13) can be cited.

[0157] 100nm<Re(550) <160nm (10)

[0158] 200nm<Re(550) <320nm (11)

[0159] Re(450) / Re(550) ≥1.00 (12)

[0160] 1.00≥Re(650) / Re(550) (13)

[0161] By stacking such a retardation film having a quarter wavelength plate function and a retardation film having a half wavelength plate function so that their slow axes intersect at approximately 60 degrees, it is possible to function as a quarter wavelength plate in a wide range (broadband) covering substantially the entire visible light region.

[0162] As a method for obtaining a composite phase difference film including a phase difference film having a 1 / 2 wavelength plate function in addition to a phase difference film having a 1 / 4 wavelength plate function, for example, methods described in Japanese Patent Publication No. 2015-163935 and WO2013 / 137464 can be cited. From the perspective of viewing angle compensation in which the tilt direction is also set to the same viewing mode as when observed from the front, it is preferred that the phase difference film having a 1 / 2 wavelength plate function is a phase difference film formed by a disc-shaped liquid crystal compound, and the phase difference film having a 1 / 4 wavelength plate function is a phase difference film formed by a rod-shaped liquid crystal compound.

[0163] The retardation film functioning as a quarter wavelength plate, the retardation film functioning as a positive C layer, and the retardation film functioning as a half wavelength plate may be tilt-oriented, cholesterically-oriented, or nematically-oriented.

[0164] The polymerizable liquid crystal compound capable of forming a phase difference film in the present invention can be appropriately selected from the field of phase difference film and the polymerizable liquid crystal compounds known in the past according to the desired optical properties. The polymerizable liquid crystal compound that can be used in the present invention can be classified into a rod-like type (rod-like liquid crystal compound) and a disc-like type (disc-like liquid crystal compound, disc-like liquid crystal compound) according to its shape, and any liquid crystal compound can also be used. In addition, a mixture of more than two rod-like liquid crystal compounds, more than two disc-like liquid crystal compounds, or rod-like liquid crystal compounds and disc-like liquid crystal compounds can be used.

[0165] The polymerizable liquid crystal compound is a liquid crystal compound having a polymerizable group. As a polymerizable liquid crystal compound, generally, the polymer (cured material) obtained by polymerizing the polymerizable liquid crystal compound in a state oriented in a specific direction alone can include a polymerizable liquid crystal compound showing positive wavelength dispersion and a polymerizable liquid crystal compound showing reverse wavelength dispersion. In the present invention, only any one polymerizable liquid crystal compound can be used, or two polymerizable liquid crystal compounds can be mixed and used. In addition, in the case where the optical laminate includes a phase difference film with a 1 / 4 wavelength plate function and a phase difference film formed by a liquid crystal cured film as a positive C plate, the polymerizable liquid crystal compounds constituting them can be the same as each other or different. For example, if the phase difference film with a 1 / 4 wavelength plate function and / or the phase difference film formed by a liquid crystal cured film as a positive C plate are respectively the cured films of the polymerizable liquid crystal composition containing the polymerizable liquid crystal compound showing so-called reverse wavelength dispersion, then the optical properties as the optical laminate are easily improved.

[0166] In the present invention, the polymerizable group possessed by the polymerizable liquid crystal compound forming the phase difference film is preferably a photopolymerizable group. A photopolymerizable group refers to a polymerizable group, and a group that can participate in a polymerization reaction by reactive species, such as active free radicals, acids, etc., generated by a photopolymerization initiator. As a photopolymerizable group, for example, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (methyl) acryloyl, oxiranyl, and oxetane can be cited. Among them, (methyl) acryloyl, vinyloxy, oxiranyl and oxetane are preferred, and acryloyl is more preferred.

[0167] The liquid crystal properties displayed by the polymerizable liquid crystal compound can be thermotropic liquid crystal or lyotropic liquid crystal. From the aspect of being able to perform dense film thickness control, thermotropic liquid crystal is preferred. In addition, as the phase sequence structure in the thermotropic liquid crystal, it can be nematic liquid crystal, smectic liquid crystal, or discotic liquid crystal. The polymerizable liquid crystal compound can be used alone or in combination of two or more.

[0168] In the present invention, the phase difference film can be configured to include an orientation film. The orientation film has an orientation restriction force that allows the polymerizable liquid crystal compound to be oriented in the desired direction. By applying a polymerizable liquid crystal composition on the orientation film, it is easy to obtain a phase difference film oriented with good precision. As an orientation film, it is preferably an orientation film having a solvent resistance that will not be dissolved by the coating of a polymerizable liquid crystal composition, and having a heat-resistant orientation film in a heating treatment for the removal of a solvent and the orientation of a polymerizable liquid crystal compound. As an orientation film, an orientation film including an oriented polymer, a light orientation film, and a groove orientation film having a concave-convex pattern and a plurality of grooves on the surface, a stretched film stretched in the orientation direction, etc. can be cited. These various orientation films can be appropriately selected from the orientation films previously known in the field according to the desired orientation restriction force.

[0169] In one embodiment of the present invention, as a horizontal alignment film having an alignment restraining force for aligning the polymerizable liquid crystal compound in the horizontal direction, a photo-alignment film is preferred from the viewpoint of the accuracy and quality of the alignment angle. The photo-alignment film is also advantageous in that the direction of the alignment restraining force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0170] The photo-alignment film is usually obtained by applying a composition containing a polymer, oligomer or monomer having a photoreactive group and a solvent (hereinafter, also referred to as a "photo-alignment film-forming composition") to a substrate, etc., and irradiating it with polarized light (preferably polarized UV light). If the polymer contained in the photo-alignment film-forming composition has a reactive group (e.g., a (meth)acryloyl group) that is the same as the functional group of the polymerizable group of the polymerizable liquid crystal compound forming the phase difference film, there is a tendency for the adhesion between the cured layer of the polymerizable liquid crystal compound and the alignment film to be improved.

[0171] Photoreactive groups refer to groups that generate liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreactions that are the origin of the liquid crystal orientation ability, such as the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules generated by light irradiation, can be cited. Among them, from the aspect of excellent orientation, groups that participate in dimerization reaction or photocrosslinking reaction are preferred. As a photoreactive group, a group having an unsaturated bond, especially a double bond, is preferred, and a group having at least one selected from a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond) is particularly preferred.

[0172] In order to impart an orientation restricting force to the oriented film, a rubbing treatment (rubbing method) may be performed as required. As a method of imparting an orientation restricting force by the rubbing method, there can be cited a method of bringing an oriented polymer film formed on the surface of a substrate by coating an oriented polymer composition on a substrate and annealing the oriented polymer composition into contact with a rubbing roller wound with a rubbing cloth and rotating. During the rubbing treatment, if masking is performed, multiple regions (patterns) with different orientation directions can also be formed on the oriented film.

[0173] In the case where the optical laminate of the present invention includes a composite phase difference film as a phase difference film, the multiple phase difference films included can be bonded via adhesive layers, respectively, or the phase difference film formed by the polymer of the polymerizable liquid crystal compound can be stacked on other phase difference films via or without an orientation film. For example, in the case of a phase difference film having a 1 / 4 wavelength plate function and a phase difference film formed by a liquid crystal curing film as a positive C plate, these phase difference films can be bonded via an adhesive layer, or a phase difference film formed by a liquid crystal curing film as a positive C plate can be stacked on the phase difference film having a 1 / 4 wavelength plate function via or without an orientation film having a vertical orientation restriction force, or a phase difference film having a 1 / 4 wavelength plate function can be stacked on the phase difference film formed by a liquid crystal curing film as a positive C plate via or without an orientation film having a horizontal orientation restriction force. In the case where the optical laminate includes two or more different phase difference films on the surface of the first adhesive layer opposite to the polarizing film, the stacking order is not particularly limited. For example, a retardation film having a quarter wavelength plate function may be adjacent to the first adhesive layer, or a retardation film formed of a liquid crystal cured film as a positive C plate or a retardation film having a half wavelength plate function may be adjacent to the first adhesive layer.

[0174] As the adhesive for bonding a plurality of retardation films together, the adhesives described as the adhesive for forming the first and second adhesive layers and the like can be used.

[0175] When a phase difference film having a 1 / 4 wavelength plate function is stacked on a polarizing plate, it is preferably stacked in a manner that the slow axis (optical axis) of the phase difference film and the absorption axis of the polarizing film are substantially 45°. By stacking in a manner that the slow axis (optical axis) of the phase difference film and the absorption axis of the polarizing film are substantially 45°, the function as a circular polarizing plate can be obtained. It should be noted that substantially 45° is usually in the range of 45±5°.

[0176] The optical layered body of the present invention can be manufactured in a manner to have a desired structure depending on its application, etc., by forming a third protective film, a second adhesive layer, a first protective film, a first adhesive layer, a polarizing film, a second adhesive layer, a second protective film, a first adhesive layer and a phase difference film in an appropriate order and stacking them according to the manufacturing method described above for each layer.

[0177] For example, a polarizing plate is prepared by laminating a first protective film on one side of a polarizing film and a second protective film on the other side via an adhesive layer. Alternatively, a phase difference film is prepared on a substrate via an oriented film, and the polarizing plate and the phase difference film are bonded together using an adhesive to prepare a circular polarizing plate. Next, a third protective film is laminated on the first protective film side of the circular polarizing plate via an adhesive to obtain a Figure 1As shown, an optical laminate comprising the third protective film / the second adhesive layer / the first protective film / the first adhesive layer / the polarizing film / the second adhesive layer / the second protective film / the first adhesive layer / the phase difference film. In addition, by forming a cured resin layer on the surface of the third protective film on the opposite side of the second adhesive layer, an optical laminate comprising a cured resin layer / the third protective film / the second adhesive layer / the first protective film / the first adhesive layer / the polarizing film / the second adhesive layer / the second protective film / the first adhesive layer / the phase difference film can be obtained. In addition, by laminating other phase difference films on a circular polarizing plate via an adhesive adhesive, an optical laminate comprising, for example, the third protective film / the second adhesive layer / the first protective film / the first adhesive layer / the polarizing film / the second adhesive layer / the second protective film / the first adhesive layer / the phase difference film / the adhesive layer / the phase difference film can be obtained.

[0178] The optical laminate of the present invention is not easy to produce positive curling over time, and can suppress the mixing of microbubbles at the end of the optical laminate when assembled to the display element, so high optical performance can be expected. Therefore, the optical laminate of the present invention is suitable as a component of various display devices. In addition, since it can be stored for a long time, it is possible to reduce the discarding of the optical laminate caused by time changes.

[0179] A display device refers to a device having a display element, including a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, touch panel display devices, electron emission display devices (such as field emission display devices (FED), surface field emission display devices (SED)), electronic paper (display devices using electronic ink, electrophoretic elements, plasma display devices, projection display devices (such as grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD)) and piezoelectric ceramic displays. Liquid crystal display devices include transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, and the like. Any of liquid crystal display devices, direct-view liquid crystal display devices and projection liquid crystal display devices. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. In particular, the optical laminate of the present invention can be suitable for organic electroluminescent (EL) display devices and inorganic electroluminescent (EL) display devices, and can also be suitable for liquid crystal display devices and touch panel display devices. These display devices can show good image display characteristics by having an optical laminate of the present invention with excellent mixing suppression effect of microbubbles at the end of the optical laminate when assembled to the display element.

[0180] Example

[0181] The present invention will be described in further detail below by way of Examples and Comparative Examples, but the present invention is not limited to these Examples. "%" and "parts" in Examples and Comparative Examples refer to "mass %" and "mass parts" unless otherwise specified.

[0182] 1. Production of polarizing plate

[0183] (1) Production of polarizing film

[0184] A polyvinyl alcohol resin film with a thickness of 20 μm (average degree of polymerization of about 2400, saponification degree of 99.9 mol% or more) was longitudinally uniaxially stretched to about 5 times by dry stretching, and then immersed in pure water at a temperature of 60°C for 1 minute while maintaining the tension state, and then immersed in an aqueous solution at a temperature of 28°C with a mass ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 for 60 seconds. Then, it was immersed in an aqueous solution at a temperature of 72°C with a mass ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 for 300 seconds. Then, after washing with pure water at a temperature of 26°C for 20 seconds, it was dried at a temperature of 65°C to obtain a polarizer with a thickness of 8 μm in which iodine was adsorbed and oriented on the polyvinyl alcohol resin film.

[0185] (2) Preparation of aqueous adhesive for forming the first adhesive layer and the second adhesive layer

[0186] 3 parts by mass of carboxyl-modified polyvinyl alcohol ("KL-318" manufactured by Kuraray Co., Ltd.) was dissolved in 100 parts by mass of water to prepare a polyvinyl alcohol aqueous solution. A water-soluble polyamide epoxy resin ("Sumirez Resin 650 (30)" manufactured by Taoka Chemical Industry Co., Ltd., solid content concentration 30% by mass) was mixed in the obtained aqueous solution at a ratio of 1.5 parts by mass to 100 parts by mass of water to obtain a water-based adhesive.

[0187] (3) Preparation of polarizing plate

[0188] The above-obtained water-based adhesive is applied to one side of the polarizing film obtained above, and a protective film (1) ["ZeonorFilmZD-U" manufactured by ZEON Corporation of Japan, with a thickness of 23 μm, a cyclic polyolefin resin film (COP film)] is laminated. The above-obtained water-based adhesive is applied to the other side of the polarizing film, and a protective film (2) [a triacetylcellulose film (TAC film) with a thickness of 20 μm] is laminated. The obtained laminate is dried at a temperature of 80°C for 5 minutes, thereby obtaining a polarizing plate having protective films on both sides of the polarizing film via adhesive layers. The layer structure of the polarizing plate is protective film (1) (COP film) / water-based adhesive layer / polarizing film / water-based adhesive layer / protective film (2) (TAC film).

[0189] (4) Determination of dimensional change rate of protective film

[0190] The protective film (1) (COP film) was cut into a rectangle of 150 mm × 50 mm as a measurement sample. The long and short side dimensions were precisely measured using the image measuring device "NEXIV (VMZ-R4540)" manufactured by Nikon Corporation, and the dimensions were taken as the initial dimensions. Next, the above-mentioned measurement sample was kept in an oven at 40°C and 60% RH for 48 hours, and the long and short side dimensions were precisely measured in the same manner as the initial dimension measurement method, and the dimensions were taken as the dimensions after 48 hours. The dimensional change rates of the long and short sides were calculated using the following calculation formula, and the average value was taken as the dimensional change rate of the protective film (1).

[0191] Size change rate = (size after 48 hours - initial size) / (size after 48 hours) × 100

[0192] The dimensional change rate of the protective film (1) (COP film) was -0.01%.

[0193] The dimensional change rate of the protective film (2) (TAC film) was determined as the average value of the long side and the short side in the same manner as the protective film (1). The dimensional change rate of the protective film (2) (TAC film) was +0.02%.

[0194] 2. Preparation of a laminate including an adhesive layer

[0195] (1) Preparation of Adhesive Layer (1)

[0196] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device and a nitrogen inlet tube, 95.0 parts of n-butyl acrylate, 4.0 parts of acrylic acid, 1.0 parts of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate and 0.08 parts of 2,2'-azobisisobutyronitrile were added, and the air in the reaction vessel was replaced with nitrogen. The reaction solution was heated to 60°C while stirring under a nitrogen atmosphere, reacted for 6 hours, and then cooled to room temperature.

[0197] The weight average molecular weight of a portion of the obtained solution was measured, and the formation of a (meth)acrylate polymer of 1.8 million was confirmed. The weight average molecular weight (Mw) of the (meth)acrylic resin is a polystyrene-equivalent weight average molecular weight measured using gel permeation chromatography (GPC) under the following conditions.

[0198] [Measurement conditions]

[0199] ·GPC measuring apparatus: HLC-8020 manufactured by Tosoh Corporation

[0200] ·GPC column (passed in the following order): manufactured by Tosoh Corporation

[0201] TSK guard column HXL-H

[0202] TSK gel GMHXL (×2)

[0203] TSK gel G2000HXL

[0204] ·Test solvent: tetrahydrofuran

[0205] ·Measurement temperature: 40℃

[0206] 100 parts (solid content conversion value) of the (meth)acrylate polymer obtained in the above step, 1.5 parts (solid content conversion value) of trimethylolpropane-modified toluene diisocyanate (manufactured by Tosoh Corporation, trade name "Coronate (registered trademark) L") as an isocyanate crosslinking agent, 0.30 parts (solid content conversion value) of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM403") as a silane coupling agent, and 0.50 parts (solid content conversion value) of 1-hydroxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM403") as a UV curing agent were added. 7.5 parts (solid content conversion value) of ethoxylated isocyanuric acid triacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.: product name "A-9300") as a photopolymerization initiator and 0.5 parts (solid content conversion value) of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one (manufactured by BASF: Irgacure (registered trademark) 907) as a photopolymerization initiator are mixed, stirred thoroughly, and diluted with ethyl acetate to obtain a coating solution of the adhesive composition (1).

[0207] On the release-treated surface of a diaphragm (manufactured by Lintec: SP-PLR382190) on which a release treatment was applied on one side, the coating solution of the adhesive composition (1) obtained above was applied using an applicator in such a manner that the thickness after drying became 5 μm (measured using a digital micrometer "MH-15M" manufactured by Nikon Corporation), and then dried at a temperature of 100°C for 1 minute. On the side of the dried coating layer opposite to the side on which the diaphragm was bonded (the exposed side of the coating layer), a diaphragm (manufactured by Lintec: SP-PLR381031) on which a release treatment was applied on one side was bonded on the release-treated side. Next, using an ultraviolet irradiation device with a conveyor belt (manufactured by Fusion UV Systems, using a D bulb as the lamp), the coating layer was irradiated with ultraviolet rays (irradiation intensity 500 mW / cm 2 , cumulative light intensity 500mJ / cm 2), thereby forming an adhesive layer (1), and obtaining an adhesive layer (1) with a double-sided separator. The layer structure of the adhesive layer (1) with a double-sided separator is separator (SP-PLR382190) / adhesive layer (1) / separator (SP-PLR381031). The thickness of the adhesive layer (1) is 5 μm.

[0208] (2) Preparation of Adhesive Layer (2)

[0209] The adhesive layer (2) with a double-sided separator was obtained in the same manner as the preparation of the adhesive layer (2) except that the coating solution of the adhesive composition (2) was applied in such a manner that the thickness after drying was 15 μm. The layer structure of the adhesive layer (2) with a double-sided separator was separator (SP-PLR382190) / adhesive layer (2) / separator (SP-PLR381031). The thickness of the adhesive layer (2) was 15 μm.

[0210] (3) Determination of water vapor permeability

[0211] The water vapor permeability of the adhesive layers (1) and (2) prepared above was measured at a temperature of 40°C and a relative humidity of 90% using a water vapor permeability meter (Lyssy-L80-5000 manufactured by Lyssy Co., Ltd.), and the results were 7600 g / (m 2 ·24h).

[0212] (4) Determination of storage modulus

[0213] As a sample for measuring the storage modulus G', a sample obtained by laminating a plurality of adhesive layers (1) and (2) in such a manner that the thickness becomes 0.2 mm (measured using a digital micrometer "MH-15M" manufactured by Nikon Corporation) and punching out a cylinder having a diameter of 8 mm was used. The sample for measurement was measured by a torsional shear method under the following conditions using a viscoelasticity measuring device (manufactured by Physica Corporation, MCR300) in accordance with JIS K7244-6.

[0214] [Measurement conditions]

[0215] Normal force FN: 1N

[0216] Strain γ: 1%

[0217] Frequency: 1Hz

[0218] Temperature: 25℃

[0219] The storage modulus G' of the adhesive layers (1) and (2) was measured and found to be 125,000 Pa (0.125 MPa) at a temperature of 25°C.

[0220] (5) Determination of glass transition temperature

[0221] The glass transition temperatures of the adhesive layer (1) and the adhesive layer (2) were measured according to the following procedure.

[0222] First, 5 mg of the adhesive layer (1) or (2) was collected and placed in an aluminum pressure-capped container, which was pressed and sealed to prepare a sample for measurement. A container containing the above-mentioned sample for measurement was set in a differential scanning calorimeter (DSC) ["EXSTAR-6000DSC6220" sold by SII Nano Technology], and the temperature was lowered from 20°C to -60°C while purging nitrogen. After reaching -60°C, the temperature was kept at 10°C / min for 1 minute, and then the temperature was raised from -60°C to 150°C. After reaching 150°C, the temperature was immediately lowered to 20°C. Then, the midpoint glass transition temperature specified in JIS K 7121-1987 "Method for Determining the Transition Temperature of Plastics" was obtained from the DSC curve when the temperature was raised from -60°C to 150°C, and it was used as the glass transition temperature of the adhesive layers (1) and (2) to be measured. The results were all below 25°C.

[0223] (6) Preparation of Adhesive Layer (3)

[0224] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device and a nitrogen inlet tube, 97.0 parts of n-butyl acrylate, 1.0 parts of acrylic acid, 0.5 parts of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate and 0.08 parts of 2,2'-azobisisobutyronitrile were added, and the air in the reaction vessel was replaced with nitrogen. While stirring under a nitrogen atmosphere, the reaction solution was heated to 60°C, reacted for 6 hours, and then cooled to room temperature. The weight average molecular weight of a portion of the obtained solution was measured according to the above steps, and the formation of a (meth)acrylate polymer of 1.8 million was confirmed.

[0225] 100 parts of the (meth)acrylate polymer obtained in the above step (solid content conversion value; the same below), 0.30 parts of trimethylolpropane-modified toluene diisocyanate (manufactured by Tosoh Corporation, trade name "Coronate (registered trademark) L") as an isocyanate crosslinking agent, and 0.30 parts of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM403") as a silane coupling agent were mixed, stirred thoroughly, and diluted with ethyl acetate to obtain a coating solution of the adhesive composition (3).

[0226] The coating solution of the adhesive composition (3) obtained above was applied to the release-treated surface of a separator (SP-PLR382190 manufactured by Lintec) on one side of which a release treatment was applied, using an applicator, so that the thickness after drying was 25 μm (the thickness was measured using a digital micrometer "MH-15M" manufactured by Nikon). Then, the coating solution was dried at a temperature of 100° C. for 1 minute, and a separator (SP-PLR381031 manufactured by Lintec) on one side of which a release treatment was applied was attached to the exposed surface of the dried coating layer (the surface opposite to the surface on which the separator was laminated), thereby obtaining an adhesive layer (3) with a separator on both sides.

[0227] The storage modulus G' of the adhesive layer (3) was measured by the above procedure and was 25500 Pa (0.0255 MPa) at a temperature of 25° C. The glass transition temperature of the adhesive layer (3) was measured by the above procedure and was 25° C. or less.

[0228] 3. Preparation of a laminate including a phase difference film

[0229] (1) Preparation of phase difference film (1)

[0230] (i) Preparation of photo-alignment film-forming composition

[0231] 2 parts of the photo-alignment material having the structure shown below and 98 parts of cyclopentanone (solvent) were mixed and stirred at 80° C. for 1 hour to obtain a photo-alignment film-forming composition. The photo-alignment material having the following structure (weight average molecular weight: 50,000, m:n=50:50) was synthesized according to the method described in Japanese Patent Application Laid-Open No. 2021-196514.

[0232] Photo-oriented materials:

[0233] [Chemical formula 1]

[0234]

[0235] (ii) Preparation of polymerizable liquid crystal composition (1)

[0236] The polymerizable liquid crystal compound (X6), polymerizable liquid crystal compound (X7), leveling agent and photopolymerization initiator shown below are mixed, and N-methyl-2-pyrrolidone (NMP) is mixed in a manner such that the solid content concentration becomes 13%, and stirred for 1 hour at a temperature of 80°C to prepare a polymerizable liquid crystal composition (1). The polymerizable liquid crystal compound (X6) and the polymerizable liquid crystal compound (X7) have the structures shown below. The polymerizable liquid crystal compound (X6) is prepared in the same manner as the method described in Japanese Patent Publication No. 2019-003177. The polymerizable liquid crystal compound (X7) is prepared in the same manner as the method described in Japanese Patent Publication No. 2009-173893.

[0237] Polymerizable liquid crystal compound (X6): 90 parts

[0238] Polymerizable liquid crystal compound (X7): 10 parts

[0239] Leveling agent [BYK-361N (made by BM Chemie)]: 0.1 part

[0240] Photopolymerization initiator [Irgacure OXE-03 (manufactured by BASF Japan Co., Ltd.)]: 3 parts

[0241] Polymerizable liquid crystal compound (X6):

[0242] [Chemical formula 2]

[0243]

[0244] Polymerizable liquid crystal compound (X7):

[0245] [Chemical formula 3]

[0246]

[0247] 1 mg of polymerizable liquid crystal compound (X6) was dissolved in 10 mL of chloroform to obtain a solution. The obtained solution was added to a measuring cuvette with an optical path length of 1 cm as a measuring sample, and the measuring sample was set in an ultraviolet visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. The wavelength reaching the maximum absorbance was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the range of 300 to 400 nm was 356 nm.

[0248] (iii) Preparation of phase difference film with substrate layer (1)

[0249] The composition for forming a photo-aligned film obtained above was applied to a biaxially stretched polyethylene terephthalate (PET) film (Diafoil, manufactured by Mitsubishi Plastics Co., Ltd.) by a rod coater to obtain a coating layer. The obtained coating layer was dried at a temperature of 120°C for 2 minutes, cooled to room temperature to dry the coating layer, and then, a UV irradiation device (SPOT CURESP-9; manufactured by USHIO Electric Co., Ltd.) was used to irradiate the dried coating layer with polarized ultraviolet light of 100mJ (based on 313nm) to obtain a photo-aligned film on the PET film. The thickness of the photo-aligned film measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100nm.

[0250] The polymerizable liquid crystal composition (1) prepared above was applied to the photo-aligned film obtained on the PET film using a rod coater to form a coating layer. The formed coating layer was heated and dried at a temperature of 120°C for 2 minutes and then cooled to room temperature. The dried coating layer was irradiated with an exposure of 500 mJ / cm2 using a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) in a nitrogen atmosphere. 2 (based on 365nm) of ultraviolet light, thereby forming a cured layer (1) of a polymerizable liquid crystal composition (1) in which the polymerizable liquid crystal compound is cured in a state of orientation in the PET film surface. The thickness of the cured layer (1) measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation is 2μm. Thus, a phase difference film (1) with a substrate layer comprising a first substrate layer (PET film) / phase difference film (1) (photo-alignment film / cured layer (1)) is obtained. Here, the thickness of the phase difference film (1) composed of the photo-alignment film (100nm) and the cured layer (1) (2μm) is 2.1μm.

[0251] (2) Determination of phase difference

[0252] The phase difference film (1) side of the first phase difference film (1) with a substrate layer is subjected to a corona treatment, and the first liquid crystal phase difference layer side with a substrate layer is bonded to an inorganic glass plate via an adhesive layer (1), and the first substrate layer (PET film) is peeled off and removed to obtain a test body. The layer structure of the test body is phase difference film (1) [photo-alignment film / cured material layer (1)] / adhesive layer (1) / inorganic glass plate. The in-plane phase difference value of the test body is measured using "KOBRA-WR" manufactured by Oji Instruments Co., Ltd. The in-plane phase difference value relative to light of wavelengths 450nm, 550nm and 650nm is calculated based on the Cauchy dispersion formula obtained from the measurement results of the in-plane phase difference value of light of wavelengths 448.2nm, 498.6nm, 548.4nm, 587.3nm, 628.7nm and 748.6nm. As a result, the in-plane phase difference values ​​are Re(450)=122nm, Re(550)=140nm, Re(650)=144nm, and the relationship between the in-plane phase difference values ​​at each wavelength is as follows.

[0253] Re(450) / Re(550)=0.87

[0254] Re(650) / Re(550)=1.03

[0255] [Wherein, Re(450) represents the in-plane phase difference value relative to light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value relative to light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value relative to light with a wavelength of 650 nm.]

[0256] It should be noted that the in-plane phase difference value of the inorganic glass plate is 0 nm at wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm and 748.6 nm, and the in-plane phase difference value at 450 nm, 550 nm and 650 nm is 0 nm. Therefore, the in-plane phase difference value of the test body is the in-plane phase difference of the phase difference film (1) (photo-alignment film and cured layer (1)) constituting it.

[0257] (3) Preparation of phase difference film (2)

[0258] (i) Preparation of composition for forming vertical alignment film

[0259] A mixture was obtained by mixing 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, dipentaerythritol triacrylate and bis(2-vinyloxyethyl) ether in a ratio of 1:1:4:5 (mass ratio), and 4 parts by mass of "LUCIRIN TPO" manufactured by Ciba Japan Co., Ltd. was added as a polymerization initiator to 100 parts by mass of the obtained mixture to prepare a composition for forming a vertically oriented film.

[0260] (ii) Preparation of polymerizable liquid crystal composition (2)

[0261] The polymerizable liquid crystal composition (2) is prepared by mixing a photopolymerizable nematic liquid crystal compound ("RMM28B" manufactured by Merck) and a solvent so that the solid content becomes 1 to 1.5% by mass. The solvent used is a mixed solvent prepared by mixing methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK) and cyclohexanone (CHN) in a mass ratio (MEK:MIBK:CHN) of 35:30:35.

[0262] (iii) Preparation of phase difference film with substrate layer (2)

[0263] A single-sided release-treated polyethylene terephthalate (PET) film ("FF-50" manufactured by Unitika, Inc., supporting substrate (PET film (thickness 50 μm))) was subjected to a corona treatment on the surface opposite to the release-treated side. The vertical alignment film-forming composition prepared above was applied to the corona-treated surface using a slot coater in such a manner that the thickness after curing was 3 μm. The coated film was irradiated with 200 mJ / cm 2 The ultraviolet rays form a vertically oriented film on the single-sided release-treated PET film.

[0264] On the vertically oriented film formed on the above-mentioned single-sided release-treated PET film, a slit coater was used to apply the above-prepared polymerizable liquid crystal composition (2) in a manner such that the thickness after curing became 1 μm, thereby obtaining a coating layer. The drying temperature was set to 75°C, and the drying time was set to 120 seconds. After the coating layer was dried, ultraviolet rays were irradiated to polymerize the polymerizable liquid crystal compound to form a cured layer (2). Thus, a retardation film (2) with a substrate layer comprising a single-sided release-treated PET film / retardation film (2) (vertically oriented film / cured layer (2)) was obtained. The retardation film (2) is a positive C plate.

[0265] (4) Preparation of composite phase difference film

[0266] (i) Preparation of active energy ray-curable composition (1)

[0267] 70 parts by mass of 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation),

[0268] Neopentyl glycol diglycidyl ether (trade name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts by mass,

[0269] 2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts by mass,

[0270] Cationic polymerization initiator (trade name: CPI-100_50% solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by mass (substantial solid content: 2.25 parts by mass), and

[0271] 1,4-diethoxynaphthalene: 2 parts by mass were mixed to obtain an active energy ray-curable composition (1).

[0272] (ii) Preparation of composite phase difference film with substrate layer

[0273] The phase difference film (1) with a substrate layer obtained above and the phase difference film (2) with a substrate layer are stacked via the above-prepared active energy ray-curable composition (1) in a manner that the phase difference film (1) side and the phase difference film (2) side are opposite. Next, ultraviolet rays are irradiated from the phase difference film (2) side with a substrate layer to cure the active energy ray-curable composition (1), thereby forming an adhesive layer with a thickness of 2 μm, and a composite phase difference film with a substrate layer is obtained. The composite phase difference film with a substrate layer has a layer structure of a first substrate layer (PET film) / phase difference film (1) (photo-alignment film / cured material layer (1)) / adhesive layer (cured material layer of active energy ray-curable composition (1)) / phase difference film (2) (cured material layer (2) / vertical alignment film) / second substrate layer (single-sided release treated PET film).

[0274] 4. Preparation of optical laminate (circular polarizing plate) with diaphragm

[0275] The polarizing plate obtained above was cut into a rectangle in a manner that the absorption axis direction became the long side, and the surface on the protective film (2) side (TAC film side) was subjected to corona treatment. Next, the first substrate layer (PET film) on the phase difference film (1) side of the composite phase difference film with a substrate layer obtained above was peeled off to expose the photo-alignment film, and the exposed photo-alignment film was subjected to corona treatment. The surfaces subjected to the above corona treatment, that is, the TAC film side and the photo-alignment film side, were bonded together via the above-obtained adhesive layer (2) 15 μm in a manner that the long sides were consistent with each other.

[0276] Then, the second substrate layer (single-sided demoulding treated PET film) of the phase difference film (2) with a substrate layer is peeled off to expose the vertical alignment film, and the exposed vertical alignment film surface is subjected to corona treatment, and the adhesive layer (3) exposed by peeling off one diaphragm from the adhesive layer (3) with a double-sided diaphragm is bonded thereon to obtain an optical laminate with a diaphragm. The optical laminate with a diaphragm has a layer structure of polarizing plate (first protective film / first adhesive layer / polarizing film (polarizer) / second adhesive layer / second protective film) / adhesive layer (2) / phase difference film (1) (light alignment film / cured material layer (1)) / cured material layer of active energy ray curable composition (1) / phase difference film (2) (cured material layer (2) / vertical alignment film) / adhesive layer (3) / diaphragm. In addition, the slow axis of the cured material layer (1) constituting the phase difference film (1) intersects at 45 degrees in the plane relative to the absorption axis of the polarizer.

[0277] 5. Preparation of the third protective film

[0278] (1) Preparation of transparent hard coating

[0279] (i) Preparation of a solution for forming a cured resin layer

[0280] A solution having a solid content concentration of 40% by weight was prepared by mixing 50 parts by weight of an ultraviolet curable urethane acrylate monomer (refractive index 1.51), 50 parts by weight of an ultraviolet curable acrylate monomer (refractive index 1.51), 5 parts by weight of a benzophenone photopolymerization initiator, and toluene.

[0281] (ii) Preparation of transparent hard coating film

[0282] The solution obtained above was applied on a long resin film and dried at 120° C. for 5 minutes and then cured by ultraviolet irradiation to form a clear hard coat layer (cured resin layer) with a flat surface and a thickness of about 4 μm, thereby producing a long clear hard coat film.

[0283] As a resin film,

[0284] A triacetyl cellulose film having a thickness of 25 μm was used as a clear hard coat film (1).

[0285] A triacetyl cellulose film having a thickness of 40 μm was used as a clear hard coat film (2).

[0286] A triacetyl cellulose film having a thickness of 60 μm was used as a clear hard coat film (3).

[0287] A triacetyl cellulose film having a thickness of 80 μm was used as a clear hard coat film (4).

[0288] As the clear hard coat film (5), a film of an acrylic film (polymethyl methacrylate polymer film) having a thickness of 60 μm was used.

[0289] (2) Determination of dimensional change rate

[0290] A sample of 150 mm × 50 mm in size is cut out from the produced long strip of transparent hard coating film (1). At this time, the sample is cut out in such a way that the long side (150 mm) of the sample is at 45° relative to the length direction of the long strip of transparent hard coating film (1). This is used as a measurement sample and is set in a Nikon image measuring device "NEXIV (VMZ-R4540)" with the transparent hard coating side facing upward, and the dimensions of the long side and the short side are precisely measured as the initial dimensions. Next, after keeping it in an oven at 40°C and 60% RH for 48 hours, the dimensions of the long side and the short side are precisely measured in the same way, and are used as the dimensions after 48 hours. The dimensional change rate of the long side and the short side is calculated by the following calculation formula, and the average value thereof is used as the dimensional change rate of the transparent hard coating film (1).

[0291] Size change rate = (size after 48 hours - initial size) / (size after 48 hours) × 100

[0292] The dimensional change rate of each long side and the dimensional change rate of each short side of the clear hard coat film (2) to the clear hard coat film (5) were measured in the same manner as above, and the dimensional change rate of each film was determined from the average value.

[0293] [Table 1]

[0294]

[0295] <Example 1>

[0296] The COP film surface of the optical laminate with a diaphragm and the TAC film surface of the transparent hard coat (1) were subjected to corona treatment and laminated via an adhesive layer (2). The samples were cut into 150 mm × 50 mm sizes by observing the cured resin layer of the transparent hard coat (1) so that the optical axis of the polarizing film was rotated 45° clockwise based on the long side and the optical axis of the retardation film was further rotated 45° clockwise relative to the optical axis of the polarizing film, thereby obtaining samples.

[0297] The optical laminate of Example 1 comprises a clear hard coat film (1) (cured resin layer / TAC film) / adhesive layer (2) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator. The peeling force when the clear hard coat film (1) in the optical laminate of Example 1 is peeled off from the optical laminate is 1 N / 25 mm or more.

[0298] <Example 2>

[0299] A sample was obtained by the same method as in Example 1 except that the pressure-sensitive adhesive layer (2) used to bond the clear hard coat film (1) to the polarizing plate was changed to the pressure-sensitive adhesive layer (1).

[0300] The optical laminate of Example 2 comprises a clear hard coat film (1) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator. The peeling force when the clear hard coat film (1) in the optical laminate of Example 2 is peeled off from the optical laminate is 1 N / 25 mm or more.

[0301] <Example 3>

[0302] A sample was obtained by the same method as in Example 2 except that the clear hard coat film (1) was changed to the clear hard coat film (2).

[0303] The optical laminate of Example 3 comprises a clear hard coat film (2) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator. The peeling force when the clear hard coat film (2) in the optical laminate of Example 3 is peeled off from the optical laminate is 1 N / 25 mm or more.

[0304] <Example 4>

[0305] A sample was obtained by the same method as in Example 2 except that the clear hard coat film (1) was changed to the clear hard coat film (3).

[0306] The optical laminate of Example 4 comprises a clear hard coat film (3) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator. The peeling force when the clear hard coat film (3) in the optical laminate of Example 4 is peeled off from the optical laminate is 1 N / 25 mm or more.

[0307] <Example 5>

[0308] A sample was obtained by the same method as in Example 2 except that the clear hard coat film (1) was changed to the clear hard coat film (5).

[0309] The optical laminate of Example 5 comprises a clear hard coat film (5) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator. The peeling force when the clear hard coat film (5) in the optical laminate of Example 5 is peeled off from the optical laminate is 1 N / 25 mm or more.

[0310] <Comparative Example 1>

[0311] Without laminating a transparent hard coat film, the optical laminate with a diaphragm was observed from the polarizing plate side and the sample was cut into a size of 150 mm × 50 mm in such a manner that the optical axis of the polarizing film was arranged to be rotated 45° clockwise based on the long side and the slow axis of the phase difference film was further arranged to be rotated 45° clockwise relative to the absorption axis of the polarizing film.

[0312] The optical laminate of Comparative Example 1 comprises a polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator.

[0313] <Comparative Example 2>

[0314] A sample was obtained by the same method as in Example 2 except that the clear hard coat film (1) was changed to the clear hard coat film (4).

[0315] The optical laminate of Comparative Example 2 comprises a clear hard coat film (4) (cured resin layer / acrylic film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photo-alignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) / adhesive layer (3) / separator. The peeling force when the clear hard coat film (5) in the optical laminate of Comparative Example 2 is peeled off from the optical laminate is 1 N / 25 mm or more.

[0316] <Reference example>

[0317] A sample was obtained by the same method as in Comparative Example 1, except that the phase difference film (1) (photo-alignment film / cured layer (1)) / cured layer of the active energy ray-curable composition (1) / phase difference film (2) (cured layer (2) / vertical alignment film) was changed to "PURE-ACE RM" (phase difference film) manufactured by Teijin Ltd.

[0318] The optical laminate of Reference Example 1 includes polarizing plate (first protective film / first adhesive layer / polarizing film / second adhesive layer / second protective film) / adhesive layer (2) / PURE-ACE RM / adhesive layer (3) / separator.

[0319] Evaluation of optical laminates

[0320] (1) Curl measurement

[0321] After peeling off the diaphragm on the adhesive layer (3) side of each chip sample, place the adhesive layer (3) upward and put it into a 40°C, 60% RH oven for 48 hours. After taking it out, immediately place it on a "DAISO silicon pot mat" in contact with the adhesive layer (3).

[0322] The curl heights of the four corners of the chip sample were measured with a ruler, and the maximum curl amount was taken as the measured value.

[0323] (2) Observation of the degree of bubble mixing

[0324] The samples were placed in a 40°C, 60% RH oven for 48 hours, and immediately after being taken out, the diaphragm on the adhesive layer (3) side of the chip sample was peeled off, and then the samples were laminated to an alkali-free glass plate ("Eagle-XG" manufactured by Corning) using a roller. After being subjected to autoclave treatment, the number of bubbles was counted at two locations on the 50 mm side of the sample using a magnifying glass, and the evaluation was performed based on the following criteria. The results are shown in Tables 2 and 3.

[0325] [Evaluation Criteria]

[0326] A: There is less than 1 bubble larger than 50μm

[0327] B: There are 1 or more and less than 5 bubbles larger than 50 μm

[0328] C: The number of bubbles larger than 50 μm is 5 or more and less than 10

[0329] D: The number of bubbles larger than 50 μm is 10 or more and less than 15 [Table 2]

[0330]

[0331] [Table 3]

[0332]

Claims

1. An optical laminate, wherein a third protective film is laminated on the first polarizer protective film side of a circularly polarizing plate having a first polarizer protective film, a first adhesive layer, a polyvinyl alcohol-based polarizing film, a second adhesive layer, a second polarizer protective film, a first adhesive layer, and a phase difference film formed of a polymer of a polymerizable liquid crystal compound adjacent to each other in this order, via a second adhesive layer, The thickness of the phase difference film is 0.5 μm to 10 μm. After 48 hours under an environment of a temperature of 40° C. and a relative humidity of 60%, the dimensional deformation rate H1 of the first polarizer protective film, the dimensional deformation rate H2 of the second polarizer protective film, and the dimensional deformation rate H3 of the third polarizer protective film satisfy the following equations (1) and (2): -0.300≤H1-H2≤-0.001 (1) -0.040≤(H3+H1)-H2≤0.100 (2).

2. The optical layered body according to claim 1, wherein: The thickness T2 of the second polarizer protective film and the thickness T3 of the third protective film satisfy the following formula (3): 45≤(T3 / T2) ×100≤350 (3).

3. The optical layered body according to claim 1, wherein: The thickness of the third protective film is 10 μm to 100 μm.

4. The optical laminate according to claim 1, wherein: The third protective film further includes a cured resin layer on the side opposite to the circularly polarizing plate side.

5. The optical layered body according to claim 1, wherein: The third protective film is a triacetyl cellulose film or a polymethyl methacrylate polymer film.

6. The optical layered body according to claim 1, wherein: The peeling force when the third protective film is peeled off from the optical laminate is 1 N / 25 mm or more. 7 . An organic EL display device comprising the optical laminate according to claim 1 .

Citation Information

Patent Citations

  • Compound, optical film, and manufacturing method for optical film

    JP2009173893A

  • Optical film

    JP2015163935A

  • Polymerizable liquid crystal composition and retardation plate

    JP2019003177A

  • Polarizing film, polarizing plate, optical laminate, elliptical polarizing plate, organic el display, and flexible image display device

    JP2021196514A

  • Laminate

    JP2022096970A